Tranformasi Pembelajaran Bahasa Arab : Menavigasi Tantangan dan Peluang di Indonesia Pada Era Digital - Ashrafah Alaifi Aulia; Dini Febria Arifina; Mhd Hasan Basri Batu Bara; Yuyun Jelita Jabat; Sahkholid Nasution (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research was conducted to describe how the journey of the transformation of Arabic language learning in Indonesia, especially on the opportunities and challenges in the digital era that will have an impact on education. The changing times that brought Indonesia to be more developed also made Arabic language learning undergo changes. Arabic, which is present in Indonesia as a religious language, must now also begin to be realized and developed its presence. This research also seeks to reveal how attitudes must be faced when there are challenges of digitalization in the use of Arabic language learning. The author chooses to use a type of qualitative research method through a literature study approach which is then continued by descriptive analysis techniques through the Miles Matthew theory. This theory conducts qualitative research through four approaches, namely: Data collection, data redaction, data presentation and conclusion (presentation of verification). Data acquisition is taken from several sources of literature that match the research theme and then processed with several ideas and thoughts of the author. The results showed that among several opportunities for Arabic language learning in Indonesia in the era of digitalization, namely: The emergence of various online platforms, traditional learning towards application-based learning, a more active and interesting learning experience, then can increase students' interest in learninglearning, As for some of the challenges faced.